MOTIVATION OF STUDENTS WITH DISABILITIES IN PURSUING HIGHER EDUCATION IN SUKABUMI - Mutya Intan Dwi Ningrat; Luthpi Saepuloh; Heni Wulandari (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2026)
Students with disabilities continue to face various challenges in pursuing higher education, particularly in non-metropolitan areas such as Sukabumi. Limited facilities, social stigma, and the lack of optimal inclusive education services may affect their learning motivation. This study aims to analyze the motivation of students with disabilities in pursuing higher education in Sukabumi based on Self-Determination Theory (SDT), which emphasizes three basic psychological needs: autonomy, competence, and relatedness. This research employed a descriptive qualitative approach involving 23 students with disabilities from seven higher education institutions in the Sukabumi region. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that students’ motivation is influenced by internal factors such as the desire for independence, self-actualization, and self-affirmation, as well as external factors including family support, social environment, and educational institutions. The fulfillment of autonomy, competence, and relatedness plays an important role in sustaining motivation and perseverance among students with disabilities in completing higher education.